2007
DOI: 10.1155/2007/84835
|View full text |Cite
|
Sign up to set email alerts
|

WCDMA Multiservice Uplink Capacity of Highways Cigar-Shaped Microcells

Abstract: The multiservice uplink capacity and the interference (intracellular and intercellular) statistics (mean and variance) of the sectors of cigar-shaped wideband code-division multiple access (WCDMA) microcell are studied using a model of 5 highway microcells in rural zone. The two-slope propagation loss model with lognormal shadowing is used in the analysis. The capacity and the interference statistics of the microcell are studied for different sector ranges, antenna side lobe levels, standard deviation of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…1 and 2 represent the effect of shadowing (loss deviation from the mean value). Practical values of 1 , 2 , 1 , 2 and R b are [9] as follows: Figure 1 shows the sector's antenna azimuth radiation pattern and the microcell azimuth coverage. In [9], it has been shown that a model of only five microcells is sufficient for the uplink capacity analysis.…”
Section: Propagation Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…1 and 2 represent the effect of shadowing (loss deviation from the mean value). Practical values of 1 , 2 , 1 , 2 and R b are [9] as follows: Figure 1 shows the sector's antenna azimuth radiation pattern and the microcell azimuth coverage. In [9], it has been shown that a model of only five microcells is sufficient for the uplink capacity analysis.…”
Section: Propagation Modelmentioning
confidence: 99%
“…They have concluded that the twoslope propagation model is the most adequate to be used in the study of the microcells capacity. In [9], the WCDMA multiservice uplink capacity of highways cigar-shaped microcells has been given. The effect of the expected value and the variance of the multi-user interference have been used in the analysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In [9], the W-CDMA uplink practical capacity and interference statistics of rural highways cigar-shaped microcells with imperfect power control and finite transmitted power have been given where the two-slope model of propagation has been used to calculate the propagation loss. In [10], the WCDMA multiservice (voice and data) uplink capacity of highways cigar-shaped microcells has been studied.…”
Section: Introductionmentioning
confidence: 99%
“…In [7], the W-CDMA uplink capacity and interference statistics of rural highways cigar-shaped microcells with imperfect power control and uniform distribution of users were obtained. In [8] which represent one of the newest works in this area, the WCDMA multiservice uplink capacity of highways cigar-shaped microcells has been given assuming simultaneous voice and data services. The WCDMA uplink capacity and interference statistics of highways shaped microcells with imperfect power control and finite transmitted power have been presented in [9].…”
mentioning
confidence: 99%